KAJIAN NILAI-NILAI TINDAK TUTUR BERBAHASA SANTUN ANTARA PENJUAL DAN PEMBELI DI PASAR TRADISIONAL - Utami, Sri (Jurnal Likhitaprajna, 2019)
Sellers and buyers use language as a means to convey their intentions to reach an agreement. The purpose of this study was to describe the form of speech acts and types of illocutionary speech acts found in the communication of sellers and buyers in the Madyopuro Traditional Market Malang. This research was conducted at Madyopuro Malang Traditional Market. The subject of this research is the speech of sellers and buyers at the Madyopuro Traditional Market Malang. The object of this research is speech act. Research data collection is carried out using the refer method. The data is listened to by using record and note techniques. Meanwhile, the data analysis used is through the criteria for determining the type of speech act. The results of the study can be described as follows. 1) The form of speech acts found in communication between sellers and buyers in the Madyopuro Malang Traditional Market, namely speech acts locution, illocutionary speech acts and perlocution speech acts. 2) The type of speech activism found in the communication of sellers and buyers in the Madyopuro Malang Traditional Market namely statement location, order localization and question location. 3) Types of illocutionary speech acts found in communication between sellers and buyers in the Madyopuro Malang Traditional Market, namely assertive, directive, commissive and expressive. In communication between sellers and buyers in the Madyapuro Malang Traditional Market no type of declaration was found. This is due to the fact that no form of speech is found that connects the content of the speech with reality. 4) Types of perlokusi speech acts contained in the communication of sellers and buyers in Madyopuro Malang Traditional Market, namely verbal and nonverbal verbal perlocution. Keywords: speech acts, sellers, buyers, traditional markets